2008
DOI: 10.1007/s10804-007-9034-3
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity in Emerging Adulthood: Familial Variables and Adjustment

Abstract: The current study is an examination of the familial variables associated with the expression of intrinsic and extrinsic religiosity and the relationship between religiosity and adjustment in emerging adulthood. Three hundred and five emerging adults completed questionnaires regarding their religiosity, psychological adjustment, and several familial variables. Parental divorce, perceived parental marital satisfaction, and family support were found to relate to religiosity. Additionally, those classified as intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Moreover, in light of the generally pluralistic-religious situation of contemporary society (Streib, 2003), it is possible that variations in religious gender differences within as well as between religious communities may exist. However, religious subgroup gender differences have not yet been fully explored due to broad research scopes (e.g., Smith & Snell, 2009), inclusive analyses (e.g., Arnett & Jensen, 2002), and the omission of the information from demographic questionnaires (e.g., Milevsky & Leh, 2008). Furthermore, it has been suggested that religious measures may be differentially sensitive to levels of religious activity as expressed by differing religious subgroups in addition to religious affiliation (Loewenthal, MacLeod, & Cinnirella, 2002;Stoppa & Lefkowitz, 2010).…”
Section: A Critical Review Of Prior Researchmentioning
confidence: 99%
“…Moreover, in light of the generally pluralistic-religious situation of contemporary society (Streib, 2003), it is possible that variations in religious gender differences within as well as between religious communities may exist. However, religious subgroup gender differences have not yet been fully explored due to broad research scopes (e.g., Smith & Snell, 2009), inclusive analyses (e.g., Arnett & Jensen, 2002), and the omission of the information from demographic questionnaires (e.g., Milevsky & Leh, 2008). Furthermore, it has been suggested that religious measures may be differentially sensitive to levels of religious activity as expressed by differing religious subgroups in addition to religious affiliation (Loewenthal, MacLeod, & Cinnirella, 2002;Stoppa & Lefkowitz, 2010).…”
Section: A Critical Review Of Prior Researchmentioning
confidence: 99%
“…In this research, religion is viewed as a set of beliefs, rituals and behavioural codes in life considered to be sacred by their followers. Milevsky and Levitt (2004) are of the opinion that it would be interesting to examine religiosity in adolescence and recent reports (e.g., Milevsky & Leh, 2008) documented the importance of religiosity in the lives of adolescents and young adults. Cotton, McGrady, and Rosenthal (2010) explained that unique developmental changes in cognitive, social and emotional aspects influence the expression of religiosity or spirituality in adolescents.…”
mentioning
confidence: 99%
“…Specifically, when emerging adults and their mothers report higher levels of spiritual disclosure, they also tend to experience higher levels of relationship satisfaction, conflict resolution strategies, and general disclosure (Brelsford and Mahoney 2008). Similarly, Milevsky and Leh (2008) found that both mother and father support was related to emerging adults' religious activity and importance.…”
Section: Socializing Agentsmentioning
confidence: 88%